Fabrication and performance of PSf/CA ultrafiltration membranes: effect of additives for fouling resistance and selective polyphenol removal from apple juice - Wae Abdulkadir Usin, Wan Aisyah Fadilah; Md. Yunos, Khairul Faezah; Mohd. Amin, Nor Amaiza; Samsu Baharuddin, Azhari (College of Natural Resources, North Carolina State University, 2019)
This work focused on the addition of different pore formation-controlling agent to a polysulfone/cellulose acetate blend membrane via immersion precipitation using phase inversion technique to improve the fouling resistance and selective polyphenol removal of apple juice. The membranes were prepared by blending hydrophilic polyvinylpyrrolidone (PVP) and amphiphilic Pluronic F127 (Plu) with polysulfone/cellulose acetate matrix in N-methyl-2-pyrrolidone. The morphology, mechanical strength, flux permeation, flux recovery ratio, and polyphenol separation of these membranes were characterized. It was found that the fabricated membranes with addition of PVP and Plu were more effective than the membrane without a pore formation-controlling agent. The flux recovery of the membranes with combined pore formers after ultrafiltration of bovine serum albumin increased from 12.4% to 66.9%. The selectivity of polyphenols increased from 6% to 79% with an improved flux recovery of 79%, which shows the reduction of yellowish-brown pigment in apple juice.